A correlative study between maternal hemoglobin concentration during third trimester and fetal birth weight of babies born at Kathmandu Medical College and Teaching Hospital - Shrestha, Anup; Shrestha, Sabina (Journal of Pathology of Nepal, 2020)
Background: Anemia is one of the commonest health problems faced by pregnant women in both developing and developed countries. Maternal anemia is a potential risk factor for fatal outcomes like low birth weight and preterm delivery. This study intended at comparing the birth weight of the babies who were born to mothers with and without anemia during the third trimesters. Materials and methods: This study is a descriptive, cross-sectional study conducted at Kathmandu Medical College, Teaching Hospital from July 2019 to June 2020. The third-trimester hemoglobin of mothers was recorded along with the birth weight of their respective babies. Mothers with regular antenatal care visits at this hospital were included and the known causes for anemia like renal disorders, twin pregnancies, and others were excluded from the study. The third-trimester hemoglobin level of all pregnant females was correlated with the birth weight of the babies. Results: Out of a total of 2417 pregnant women, 317 (13%) had anemia. The overall prevalence of low birth weight was 12%. Out of 317 anemic mothers, 99 (31%) delivered low birth weight babies. Among those 99 low birth weight babies, 30 (30%) were preterm and 69 (70%) were term babies with the prevalence of low birth weight in anemic mothers being 31%. The correlation between maternal hemoglobin and birth weight was found to be statistically significant. Conclusions: Despite regular antenatal care, maternal anemia still prevails, affecting neonatal birth weight. There was a statistically significant correlation between maternal hemoglobin and birth weight (p-value <0.0001).